2003
DOI: 10.1152/ajpgi.00307.2002
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of dextran sulfate colitis by butyrate: role of heat shock protein 70 and NF-κB

Abstract: Butyrate enemas have been demonstrated to ameliorate inflammation in ulcerative colitis. The mechanism of this protective effect of butyrate is not known, and this study examines the effect of butyrate on epithelial function, inducible heat shock protein 70 (HSP70) expression, and NF-kappaB activation in experimental colitis. Colitis was induced in rats by oral dextran sulfate sodium (DSS) and by butyrate or saline enemas. Mucosal barrier function was assessed by electrical resistance and [14C]mannitol permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 48 publications
4
81
0
Order By: Relevance
“…In previous studies, it was shown that butyrate can inhibit the binding of NF-B to DNA (12,15,47). In contrast, in the reporter gene assays, butyrate enhanced the transcriptional activity driven by NF-B sites and the TNF␣ promoter in a dose-dependent manner ( Figures 3A and B).…”
Section: Discussionmentioning
confidence: 74%
“…In previous studies, it was shown that butyrate can inhibit the binding of NF-B to DNA (12,15,47). In contrast, in the reporter gene assays, butyrate enhanced the transcriptional activity driven by NF-B sites and the TNF␣ promoter in a dose-dependent manner ( Figures 3A and B).…”
Section: Discussionmentioning
confidence: 74%
“…Because some HSPs have been reported to be overexpressed in the intestinal tissues of IBD patients (19,20,23) and in an animal model of IBD (21)(22)(23). HSF1 and HSPs are thought to be involved in the pathogenesis of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The production of these pro-inflammatory cytokines is mediated mainly by transcriptional activation of nuclear factor κB (NF-κB) and mitogen activated protein kinase (MAPK) pathways (Malago et al, 2002;Ke et al, 2013). Several therapeutic interventions such as butyrate enemas modulate the activation of these pathways and suppress the production of pro-inflammatory cytokines to protect the colon against inflammatory injury (Venkatraman et al, 2003;Malago et al, 2005;Ke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%